Melatonin and Synthetic Melatoninergic Agonists in Psychiatric and Age-associated Disorders: Successful and Unsuccessful Approaches - Hardeland, Rüdiger (Current Pharmaceutical Design, 2016)
Melatonin and the following approved or investigational synthetic melatoninergic agonists are compared with regard to half-life, receptor affinity, metabolism and additional properties: TIK-301, piromelatine, GG-012, AH-001, AH-017, agomelatine, ramelteon, GR 196429, MA-2, tasimelteon, UCM765, and UCM924. Apart from restrictions from the respective approvals, theoretical limits of treatment are outlined as they result from chronobiological, genetic, epigenetic, degenerative or toxicological considerations. Melatoninergic agonists have been shown to reliably entrain circadian rhythms, if chronobiological phase response rules are followed. This allows the treatment of dysphased rhythms, circadian rhythm sleep disorders, and forms of depression with an etiology of circadian dysfunction, such as bipolar disorder and seasonal affective disorders. Entrainment and induction of sleep onset requires only short actions, with low doses of immediate-release melatonin likely to be sufficient. However, sleep maintenance is poorly supported by any of the agonists, despite statistically demonstrable effects. The combinations of melatoninergic properties with the inhibition of 5-HT2C receptors, as in agomelatine and TIK-30, may result in moderate direct antidepressive actions. Other limits of a successful treatment can arise from genetic or epigenetic silencing of melatonin receptor genes, perhaps also from imbalances between parallel signaling pathways in receptor mutants, and from neurodegeneration, especially in the suprachiasmatic nucleus. Variants of circadian clock genes cause rhythm deviations that may be corrected by melatoninergic treatment, provided that the spontaneous oscillation period is not beyond the entrainment range. Caveats concerning melatonin’s roles as an immune modulator and in certain pathologies, such as Parkinson’s disease, as well as toxicological considerations for agonists and their metabolites are also addressed.
Keywords: ramelteon